Effect of Tenofovir Disoproxil Fumarate and Emtricitabine on nasopharyngeal SARS-CoV-2 viral load burden amongst outpatients with COVID-19: A pilot, randomized, open-label phase 2 trial. (August 2021) - Parienti, Jean-Jacques; Prazuck, Thierry; Peyro-Saint-Paul, Laure; Fournier, Anna; Valentin, Cécile; Brucato, Sylvie; Verdon, Renaud; Sève, Aymeric; Colin, Mathilda; Lesne, Fabien; Guinard, Jérome; Ar Gouilh, Meriadeg; et al.
Abstract: Background: Tenofovir and emtricitabine interfere with the SARS CoV-2 ribonucleic acid (RNA)-dependent RNA polymerase (RdRp). Several cohorts reported that people treated by tenofovir disoproxil fumarate and emtricitabine are less likely to develop SARS CoV-2 infection and related severe COVID-19. Methods: We conducted a pilot randomized, open-label, controlled, phase 2 trial at two hospitals in France. Eligible patients were consecutive outpatients (aged ≥18 years) with RT-PCR-confirmed SARS-CoV-2 infection and an interval from symptom onset to enrolment of 7 days or less. Patients were randomly assigned in a 1:1 ratio to receive oral tenofovir disoproxil fumarate and emtricitabine (2 pills on day 1 followed by 1 pill per day on days 2–7) or the standard of care. The primary and secondary endpoints were SARS-CoV-2 viral clearance from baseline assessed by cycle threshold (Ct) RT-PCR on nasopharyngeal swab collected at day 4 and day 7, respectively. A higher Ct corresponds to a lower SARS CoV-2 viral burden. Other endpoints were the time to recovery and the number of adverse events. This trial is registered with ClinicalTrials.gov, NCT04685512. Findings: From November, 20 th 2020 to March, 19 th 2021, 60 patients were enrolled and randomly assigned to a treatment group (30 to tenofovir disoproxil fumarate and emtricitabine and 30 to standard of care). The median number of days from symptom onset to inclusion was 4 days (IQR 3–5) in both groups. Amongst patients who received tenofovir disoproxil fumarate, the difference from standard of care in the increase in Ct RT-PCR from baseline was 2.3 (95% confidence interval [-0.6 to 5.2], p = 0.13) at day 4 and 2.9 (95% CI [0.1 to 5.2], p = 0.044) at day 7. At day 7, 6/30 in the tenofovir disoproxil fumarate and emtricitabine group and 3/30 in the standard of care group reported no COVID-related symptoms. Adverse events included 11 cases of gastrointestinal side effects (grade ≤ 2), three of which leaded to drug discontinuation. Three patients had COVID-19 related hospitalisation, no participant died. Interpretation: In this pilot study of outpatients adult with recent non-severe COVID-19, tenofovir disoproxil fumarate plus emtricitabine appeared to accelerate the natural clearance of nasopharyngeal SARS-CoV-2 viral burden. These findings support the conduct of larger trials of tenofovir-based therapies for the prevention and early treatment of COVID-19. Funding: No external funding.